Perceptions of Farmer Families on Children's Education in Rural Cianjur - Silfa Sofia Fiqri; Bukhori Bukhori (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2021)
Agricultural development is still considered the most important of the overall economic development, because the agricultural sector is the savior of the national economy. However, most of the farming families are classified as poor. The impact of poverty affects other lives. One of them affects the education of their children. In general, this research is based on the descriptive method, with an emphasis on giving a picture or painting an explanation of the symptoms that occur in the community or the most actual events. The research steps are from determining the method, type of data, data sources, data collection techniques to data analysis techniques, and ends with conclusions. The results showed that the socio-economic life of farming families in Sukamaju Village in Cianjur District, Cianjur Regency, was very low both in terms of socioeconomic, education and others. The factors that cause children to drop out of school in the Sukamaju Village community include economic factors; the low factor and lack of interest of the child to continue school; factor of lack of awareness and attention of parents; the absence of school infrastructure, and cultural factors. The views of parents on children's education are different, basically influenced by their educational background and socio-economic status and culture around them.